ANALYSIS METHODS COMPLEX DIAGNOSTICS OF ENTERPRISE FINANCIAL CONDITION - S. Demin; E. Dzhamay; L. Mikhailova (Вестник университета)
The article provides an overview of domestic and foreign methods of complex diagnostics of the financial condition of the company. All of the techniques aimed at assessing the risk of a crisis of the financial situation or bankruptcy. The authors identified the advantages and disadvantages of each of the models considered.